2009
DOI: 10.1007/s10522-009-9252-0
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and ageing

Abstract: Within the past three to four decades a revolution has occurred in our understanding of vitamin D and its effects. Sundry laboratory and epidemiologic studies have revealed that the active metabolite of vitamin D controls and/or ameliorates various pathologies. As presented here, there is substantive evidence that vitamin D may play a positive and important role in the ageing process.This evidence arises from detailed consideration of various biological mechanisms and processes by which vitamin D operates as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 133 publications
(133 reference statements)
2
13
0
Order By: Relevance
“…Vitamin D deficiency is extremely common among elderly persons, which is caused by insufficient sunlight exposure, decreased function of the skin to synthesize vitamin D, low dietary intake of vitamin D and etc [25]. Similar to other findings [26,27], we found the prevalence of vitamin D deficiency and insufficiency was as high as 82.4% in 903 very elderly Chinese Males.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Vitamin D deficiency is extremely common among elderly persons, which is caused by insufficient sunlight exposure, decreased function of the skin to synthesize vitamin D, low dietary intake of vitamin D and etc [25]. Similar to other findings [26,27], we found the prevalence of vitamin D deficiency and insufficiency was as high as 82.4% in 903 very elderly Chinese Males.…”
Section: Discussionsupporting
confidence: 87%
“…It was found that the subjects with hypertension had a mean serum 25 Abbreviation: BMI body mass index, PTH parathyroid hormone, β-CTXβ-C-telopeptide of type 1 collagen, P1NP N-terminal propeptide of type 1 collagen, HDL-C high-density lipoprotein cholesterol, LDL-C low-density lipoprotein cholesterol, Hs-CRP high sensitivity C-reactive protein …”
Section: The Relationship Between Serum 25(oh)d and Chronic Diseases mentioning
confidence: 99%
“…Nutritional hormesis could very well be applicable as a pro-health intervention by extending human healthspan. An example of this arises from the hormetic agent vitamin D which has been posited to play a productive and positive role by reducing susceptibility in the elderly to various chronic degenerative diseases (Hayes 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the aging process itself predisposes to vitamin D deficiency, especially because of the age-related skin structure modifications. In fact, a progressive decline in the cutaneous capacity to synthesize vitamin D from ultraviolet B radiations(35, 39) (at least partly due to the reduction of 7-dehydro-cholesterol in the skin) and an increased resistance of target organs to the vitamin D action (probably due to the reduction of VDRs(40) or post-receptorial modifications(41))(42) have been described.…”
Section: Introductionmentioning
confidence: 99%